Jurassic to Cretaceous (upper Kimmeridgian–?lower Berriasian) calcispheres from high palaeolatitudes on the Antarctic Peninsula: Local stratigraphic significance and correlations across Southern Gondwana margin and the Tethyan realm - Kietzmann, Diego Alejandro; Scasso, Roberto Adrian (Palaeogeography, Palaeoclimatology, Palaeoecology)
We report Upper Jurassic–Lower Cretaceous (Kimmeridgian-Berriasian) calcispheres from the Ameghino (Nordenskjöld) Formation at high palaeolatitudes on the northern part of the Antarctic Peninsula. The Ameghino Formation generally contains a relatively poorly preserved association of calcispheres, which are often recrystallized or replaced by silica; however, early-diagenetic calcite concretions are widespread in the mudstone–tuff sequences, and calcisphere in these contexts show very good preservation. Among the seventeen species recognized in this study, thirteen are known from the Upper Jurassic–Lower Cretaceous pelagic sediments of the Tethyan and Andean regions. The remaining three include Stomiosphaera, and two new species, that probably indicate an austral character for the calcisphere association. The following calcisphere zones previously proposed for the Tethyan realm and the Andes are confirmed for the Ameghino Formation: Carpistomiosphaera borzai, Carpistomiosphaera tithonica, Parastomiosphaera malmica, Colomisphaera tenuis, Colomisphaera fortis and Stomiosphaerina proxima. Zones indicate a late Kimmeridgian to early Berriasian age, broadly consistent with previous age assignments based on ammonites and radiolarians. However, calcisphere ages allow partial stratigraphic re-arrangement of the succession cropping out in Sobral Peninsula and support the intercalation of sandy-conglomeratic beds, deposited in submarine fan environment, between the slope-basinal facies typical of the Ameghino Formation. Facies changes suggest basin margins across the Antarctic Peninsula in a complex paleogeography with large emergent landmasses to the southwest of the study area. Possible dispersal routes along the Southern Gondwana margin occurred along the so-called Hispanic and Mozambique corridors. Identified species show a global distribution, being represented in the Andean, the Tethyan and Boreal realms. The cosmopolitan character of Mesozoic calcispheres proves their importance for interregional correlations. ...